Literature Review: Ramsay Hunt Syndrome As A Complication Of Herpes Zoster Disease - Fitriani Fitriani; Dian Amelia Abdi; Fransina R. Sarungallo; Lisa Yuniati; Fanny Iskandar (Jurnal EduHealth, 2025)
Ramsay Hunt syndrome as a complication of herpes zoster, mostly occurs in immunocompromised patients. Disruption of the immune system plays a role in the reactivation of Varicella Zoster Virus (VZV). After primary varicella infection, VZV remains and is latent in the dorsal sensory ganglion roots. Then, several decades later, this neurotropic virus can reactivate and cause shingles. Ramsay Hunt syndrome is characterized by a triad of facial paralysis, ipsilateral ear pain/otalgia accompanied by facial paralysis, and the appearance of vesicle lesions in the ear according to the dermatome of the facial nerve. The purpose of this study was to determine Ramsay Hunt Syndrome as a complication of Herpes Zoster based on immunity, VZV latency period, age, gender, clinical manifestations, and management. This study used a literature review method with a Narrative Review design. The results obtained 15 journals that included inclusion criteria, namely references in the last 5 years, according to keywords, from scientific journal references, and case report research designs. The results showed that the influence of the immune system plays a major role in the reactivation of VZV, especially in elderly patients because old age causes functional changes in T cells and monocytes that function as a defense against viruses causing VZV reactivation, so Ramsay Hunt syndrome is rarely found in children <6 years. The presence of other risk factors such as a history of malignant lymphoma, HIV infection, history of immunosuppressive therapy, history of chronic disease, history of use of immunosuppressive drugs, or history of habits (consuming alcohol) can be the cause of reactivation of Varicella Zoster Virus (VZV).